Insecticidal properties of Pinus taeda essential oil - Rodrigues Pinto Junior, Airton; Haygert Lencina, Kelen; Angelica Horbach, Micheli; Kielse, Paula; Lopes da Silva, André Luís (Revista Ceres, 2025)
This study aimed to evaluate the yield of essential oil extracted from different sample and pH compositions, as well as the insecticidal potential of Pinus taeda essential oil. For this, samples composed only of needle and composed of needle and branches were kept in solvent water at different pH (3, 4, 5 and 6). Subsequently, the oils extracted in the different pH treatments were added in a proportion of 25% to Tween® (20%) and sunflower oil (55%) forming a concentrated bioinsecticide solutions at each pH. Solutions were diluted in deionized water to final concentrations of 12.5, 6.2, 3.1 and 0% oil. The samples containing needles and branches, as well as those extracted at pH between 4 and 6, provided a higher yield of essential oil. The bioinsecticide formulations containing the highest concentrations of essential oil extracted at pH 3 showed the best results in the control of S. zeamais. The essential oil of P. taeda has potential for the preparation of bioinsecticides and can be extracted from samples containing needles and twigs in a solvent with pH 3. Bioinsecticide solutions of higher concentrations are more efficient in controlling S. zeamais after 24 hours of exposure.